1995
DOI: 10.1128/jvi.69.11.6947-6957.1995
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of cultured myoblast differentiation by the simian virus 40 large T antigen occurs after myogenin expression and Rb up-regulation and is not exerted by transformation-competent cytoplasmic mutants

Abstract: We have investigated the mechanism by which the simian virus 40 large T antigen (SVLT) interferes with the differentiation of C2 myoblasts. SVLT mutants, defective either in the Rb binding site, near the N-terminal end, in a region that affects binding to p53, or in the nuclear transport signal, were also employed to determine whether the interference was especially dependent on these functional domains. It was found that wild-type (wt) SVLT strongly inhibited the terminal differentiation of mouse C2 myoblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…However, some differences do exist between the two oncoproteins in their ability to interfere with discrete steps of myogenic differentiation. In fact, SV40 TAg inhibits muscle cell differentiation without affecting the induction of myogenin expression which occurs early in the process (Tedesco et al ., 1995). It will be interesting to investigate whether these differences between E1A and TAg can be explained by their different ability to bind various forms of p300.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some differences do exist between the two oncoproteins in their ability to interfere with discrete steps of myogenic differentiation. In fact, SV40 TAg inhibits muscle cell differentiation without affecting the induction of myogenin expression which occurs early in the process (Tedesco et al ., 1995). It will be interesting to investigate whether these differences between E1A and TAg can be explained by their different ability to bind various forms of p300.…”
Section: Discussionmentioning
confidence: 99%
“…The viral oncoproteins E1A of adenovirus and large T antigens (TAg) of both SV40 and polyomavirus share the ability to inhibit myogenic differentiation (Fogel and Defendi, 1967; Webster et al ., 1988; Braun et al ., 1992; Maione et al ., 1992; Tedesco et al ., 1995). This property has been attributed to their binding to a common region of pRb, p107 and pRb2/p130, called the ‘pocket domain’.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that this arrest occurs only after the MyoD-dependent induction of myogenin and high Rb levels; an important difference from normal C2 cells, however, is that a large part of this increased Rb is hyperphosphorylated (76). Among SVLT mutants, the ability to inhibit myogenesis correlates with capability of promoting Rb hyperphosphorylation but not with that of physically complexing Rb (76).…”
mentioning
confidence: 81%
“…The simian virus 40 large T antigen (SVLT), like many other oncogene-encoded proteins (see references 2 and 44 for reviews), when expressed in C2 myoblasts causes the arrest of differentiation (18,23,25,50,76). We have shown that this arrest occurs only after the MyoD-dependent induction of myogenin and high Rb levels; an important difference from normal C2 cells, however, is that a large part of this increased Rb is hyperphosphorylated (76). Among SVLT mutants, the ability to inhibit myogenesis correlates with capability of promoting Rb hyperphosphorylation but not with that of physically complexing Rb (76).…”
mentioning
confidence: 99%
See 1 more Smart Citation